A 220 GHz dynamic frequency divider in 0.5μm InP DHBT technology. (June 2017) - Cheng, Wei; Zhang, Youtao; Wang, Yuan; Niu, Bin; Lu, Haiyan; Chang, Long; Xie, Junling
Abstract: A high performance 3 inch 0.5 μ m InP DHBT technology with three interconnecting layers has been developed. The epitaxial layer structure and geometry parameters of the device were carefully studied to get the required performances. The 0.5 × 5 μ m 2 InP DHBTs demonstrated f t = 350 GHz, f max = 532 GHz and BV CEO = 4.8 V, which were modeled using Agilent-HBT large signal model. As a benchmark circuit, a dynamic frequency divider operating from 110 to 220 GHz has been designed, fabricated and measured with this technology. The ultra-high-speed 0.5 μ m InP DHBT technology offers a combination of ultra-high-speed and high breakdown voltage, which makes it an ideal candidate for next generation 100 GHz+ mixed signal integrated circuits.